Proceedings of the 2021 International Conference on Multimodal Interaction 2021
DOI: 10.1145/3462244.3479903
|View full text |Cite
|
Sign up to set email alerts
|

User Preferences for Calming Affective Haptic Stimuli in Social Settings

Abstract: This paper presents a survey informing a user-first approach to designing calming affective haptic stimuli by eliciting user preferences in different social scenarios. Prior affective haptics research presented users with stimuli and recorded emotional responses. By contrast this work focuses on the sensations users wish to experience and how these can be simulated using haptics. The survey (n=81) investigated which users preferences in four social situations to reduce social anxiety. Using thematic analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
(148 reference statements)
0
0
0
Order By: Relevance
“…Qualitative: We used inductive thematic analysis techniques [15,50] to analyse parents' and children's perceptions from audio recorded interviews. We did not seek inter-rater reliability because researchers may interpret the meaning of codes differently [41]. After generating transcripts, the experimenter listened to all recordings (∼5min each) and corrected any mistakes in the automatically generated transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative: We used inductive thematic analysis techniques [15,50] to analyse parents' and children's perceptions from audio recorded interviews. We did not seek inter-rater reliability because researchers may interpret the meaning of codes differently [41]. After generating transcripts, the experimenter listened to all recordings (∼5min each) and corrected any mistakes in the automatically generated transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…While still in development, this technology has been envisioned to assist humans in application scenarios that are commonly found in our daily life and social interactions such as interactive displays in urban environments (e.g., shops, train stations and shopping malls) [63], museum exhibitions [102], in cars dashboards [92], in hospitals assisting surgery [75] and in calming social settings [66]. Additionally, with the recent covid-19 pandemic, mid-air haptics has been also suggested to be a promising solution to promote a touch-free and hygienic alternative to interact with technology (public displays, elevators) in social and public spaces [50,95].…”
Section: Social Mid-air Touchmentioning
confidence: 99%
“…Thermal sensation is a fundamental part of sensory and perceptual experience [31], where thermal stimulation has association with human emotion [15,16,44,52,58]. Similarly with haptic (touch) stimulation, where several studies have shown associations with emotion and afective ratings [32,33,43,47], and has the capacity to promote empathy [27]. Given the foregoing, this work explores how augmenting news consumption experiences with haptics can infuence our afective perceptions of news, and potentially enhance empathic reactions.…”
Section: Introductionmentioning
confidence: 99%